الفقر والعدالة الاجتماعیة في ضوء السنّة النّبویة : Care for the Poor and Social Justice in the Light of Sunnah the Prophet (SAW) - Dr. Abdul Hameed Kharroob; Nura Muhammad Zawawi (Seerat Studies, 2023)
Poverty is a universal social phenomenon. There are numerous factors behind it i.e. its ratio and proportion varies from one society to another. In spite of great developments in the modern contemporary world, the impact of this phenomenon has extended to the economic, political, cultural, social and environmental aspects. The poverty is not only restricted to provide the basic needs of bread, butter, clothing, shelter, health, education and other amenities, but it also covers every aspect which has been neglected by the society. The different governing systems have been tried to tackle with this problem and many theories have been emerged to resolve this issue and give affective solutions but no affective solution has been discovered so far. Islam has a distinctive and realistic approach in tackling with the issue of poverty. Natural remedy neither scorns the poor nor describes them with negative descriptions. Indeed, its approach is integrated and balanced one to deal with this severe problem. Islam paves a way to achieve social justice and equitable distribution of wealth to fight against the poverty. It warns against the dire consequences of extreme poverty that may lead the human beings to violence. This research article shows some aspects of Prophet’s care for the poor and needy people with visionary divine approach.